Metabolism and Genetics of Helicobacter pylori: the Genome Era - Marais, Armelle (American Society for Microbiology, 1999)
The publication of the complete sequence of Helicobacter pylori 26695 in 1997 and more recently that of strain J99 has provided new insight into the biology of this organism. In this review, we attempt to analyze and interpret the information provided by sequence annotations and to compare these data with those provided by experimental analyses. After a brief description of the general features of the genomes of the two sequenced strains, the principal metabolic pathways are analyzed. In particular, the enzymes encoded by H. pylori involved in fermentative and oxidative metabolism, lipopolysaccharide biosynthesis, nucleotide biosynthesis, aerobic and anaerobic respiration, and iron and nitrogen assimilation are described, and the areas of controversy between the experimental data and those provided by the sequence annotation are discussed. The role of urease, particularly in pH homeostasis, and other specialized mechanisms developed by the bacterium to maintain its internal pH are also considered. The replicational, transcriptional, and translational apparatuses are reviewed, as is the regulatory network. The numerous findings on the metabolism of the bacteria and the paucity of gene expression regulation systems are indicative of the high level of adaptation to the human gastric environment. Arguments in favor of the diversity of H. pylori and molecular data reflecting possible mechanisms involved in this diversity are presented. Finally, we compare the numerous experimental data on the colonization factors and those provided from the genome sequence annotation, in particular for genes involved in motility and adherence of the bacterium to the gastric tissue.